Netnography: An Emerging Method of Marketing Research - A Conceptual Study - Rakesh, Sapna; Singh, Swati (Indian Journal of Marketing, 2011)
'Netnography' is a research methodology in use since the late 1990s in the fields of research related to consumer behavior and marketing. However, in India, this methodology is yet not very popular. This paper aims at developing a conceptual study on Netnography. This conceptual study presents the procedure of Netnographic research. The study also focuses upon issues related to ethical consideration in Netnographic research. This research aims at discussing the steps needed to carry out netnographic research and addresses the issue of Reliability and Validity in qualitative research methods like netnography. Research method used in this paper is secondary. This paper contributes by bringing out conceptual information related to netnography.